1988
DOI: 10.1246/bcsj.61.2031
|View full text |Cite
|
Sign up to set email alerts
|

NMR Spectroscopic Study of the Conformational Preference of Methoxycarbonyl and Methyl Substituted Thiophenecarbaldehydes. Possibility of a Hydrogen-Bond-Like Interaction between Formyl C–H and the Ester Carbonyl Group

Abstract: The predominance of planar C–H/O=C approached conformations in methyl 3-formyl-2-, 2-formyl-3-, and 4-formyl-3-thiophenecarboxylates was shown experimentally by the chemical shifts of the formyl protons, the unusually large 1JCH values of the formyl groups, and their infrared C–H and C=O absorptions. The stability of the C–H/O=C approached conformation was attributed to the hydrogen-bond-like interaction between the two groups. The considerably large positive bond population between non-bonded H/O and the addi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0

Year Published

1990
1990
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 57 publications
(25 citation statements)
references
References 18 publications
1
24
0
Order By: Relevance
“…It has been shown 31,32 that the proton-donating ability of a C-H bond can only be observed, by 1 H NMR, when this interaction occurs with strong proton acceptors in sterically favorable circumstances. In such cases, the observed downfield shift is ca.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been shown 31,32 that the proton-donating ability of a C-H bond can only be observed, by 1 H NMR, when this interaction occurs with strong proton acceptors in sterically favorable circumstances. In such cases, the observed downfield shift is ca.…”
Section: Resultsmentioning
confidence: 99%
“…[32][33][34] It has been suggested that the increase of 1 J CH coupling for a C-H bond near either an F atom or a carbonyl oxygen gives evidence of the presence of a C-H‚‚‚F or C-H‚‚‚O hydrogen bond, respectively. [32][33][34] The observed increase ranges from ca. 10 Hz, in thiophene carbaldehydes (OdC-H‚‚‚OdC interaction), 32 to 3.7 Hz, in a triptycene derivative (C(sp 3 )-H‚‚‚F interaction).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In such cases, the observed downfield shift is about 1 ± 2 ppm, [20] but becomes unobservable in the case of weaker interactions. On the other hand, several studies have focused on the relationship between CÀH ¥¥¥ X hydrogen bonding and CÀH nuclear magnetic coupling (quantified by coupling constant, 1 J CH , values).…”
Section: Spectroscopic Study Of the Effects On The Donor Groupmentioning
confidence: 97%
“…It has been shown [3,20] that the proton-donating ability of a CÀH bond can only be observed by 1 H NMR when this interaction occurs with strong proton acceptors in sterically favorable circumstances. In such cases, the observed downfield shift is about 1 ± 2 ppm, [20] but becomes unobservable in the case of weaker interactions.…”
Section: Spectroscopic Study Of the Effects On The Donor Groupmentioning
confidence: 99%